Loss of mTORC2‐induced metabolic reprogramming in monocytes uncouples migration and maturation from production of proinflammatory mediators. Issue 5 (29th September 2021) - Jangani, Maryam; Vuononvirta, Juho; Yamani, Lamya; Ward, Eleanor; Capasso, Melania; Nadkarni, Suchita; Balkwill, Frances; Marelli‐Berg, Federica
Abstract: Monocyte migration to the sites of inflammation and maturation into macrophages are key steps for their immune effector function. Here, we show that mechanistic target of rapamycin complex 2 (mTORC2)‐dependent Akt activation is instrumental for metabolic reprogramming at the early stages of macrophage‐mediated immunity. Despite an increased production of proinflammatory mediators, monocytes lacking expression of the mTORC2 component Rictor fail to efficiently migrate to inflammatory sites and fully mature into macrophages, resulting in reduced inflammatory responses in vivo. The mTORC2‐dependent phosphorylation of Akt is instrumental for the enhancement of glycolysis and mitochondrial respiration, required to sustain monocyte maturation and motility. These observations are discussed in the context of therapeutic strategies aimed at selective inhibition of mTORC2 activity. Graphical Abstract: mTORC2‐dependent Akt activation is instrumental for metabolic reprogramming at the early stages‐migration and differentiation‐of macrophage‐mediated immunity.